2019
DOI: 10.2478/bsrj-2019-023
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Tourist Revisit Intention through the Sports and Recreational Services Offered

Abstract: Background: Sports and recreational tourism are forms of tourism that imply active involvement of tourists in various sports activities during their vacation, and it can be said that the main motive of such a vacation is a sport. Objectives: This research aimed to determine the relationship between sports and recreational activities and tourist satisfaction based on the questionnaire related to the behaviour and satisfaction of tourists during their stay in Montenegro. Methods/Approach: Regression analysis has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…: Harun et al, 2018;Wu, Li, & Li, 2018), who emphasised entertainment and tourism activities that generate unforgettable tourist destination experiences and help to reinforce their revisiting intentions. A potential reason may be due to the high costs needed for activities like labour-power in developing a safety protocol in the creation of ecotourism (Markus, Perovic, Pekovic, & Popovic, 2019). In addition, interviewed international tourists gave a potential explanation that could be linked to the risk of growing environmental assets and residents' efficiency in the tourism destination.…”
Section: Hypothesismentioning
confidence: 99%
“…: Harun et al, 2018;Wu, Li, & Li, 2018), who emphasised entertainment and tourism activities that generate unforgettable tourist destination experiences and help to reinforce their revisiting intentions. A potential reason may be due to the high costs needed for activities like labour-power in developing a safety protocol in the creation of ecotourism (Markus, Perovic, Pekovic, & Popovic, 2019). In addition, interviewed international tourists gave a potential explanation that could be linked to the risk of growing environmental assets and residents' efficiency in the tourism destination.…”
Section: Hypothesismentioning
confidence: 99%
“…Overall, it could be concluded that animator competences are one of the main conditions for achieving economic benefit. Moreover, we can suggest that animations and recreational programmes, as well as animators, can allow hotels and tourist destinations to improve general expectations and tourists' satisfaction (Markus, Perovic, Pekovic, & Popovic, 2019). Managerial implications of this paper are various.…”
Section: Discussionmentioning
confidence: 92%
“…Cleas (2007, p. 45) points out that only satisfied consumers represent real, intangible, economic assets. According to the previous studies, the animation program offer has impact on the satisfaction of the guest (Markus et al, 2019;Peković et al, 2019;Perović et al, 2018;Albayrak, Caber i Öz, 2016;Cetin i Walls, 2015;Demir i Demir, 2015;Laškarin, 2015;Ababneh, 2013;Korkutata i Yılmaz, 2013;AbuKhalifeh i Mat Som, 2012;Mikulić i Prebežac, 2011;Türkay, Camarda i Badau, 2010;Cerović, 2008;Glinia et al, 2001;Glinia et al, 2001a;Jadrešić, 2001;Corbaci, 1993).…”
Section: The Influence Of Animation Programs On Guest Satisfaction and Guest Loyaltymentioning
confidence: 98%